Maternal colonisation with Streptococcus agalactiae, and associated stillbirth and neonatal disease in coastal Kenya - Berkley, J; Seale, A; Koech, A; Sheppard, A; Barsosio, H; Langat, J; Anyango, E; Mwarumba, S; Makio, S; Morpeth, S; Anampiu, K; Vaughan, A; et al. (Nature Publishing Group, 2016)
Streptococcus agalactiae (Group B Streptococcus, GBS) causes neonatal disease and stillbirth, but its burden in sub-Saharan Africa is uncertain. We assessed maternal recto-vaginal GBS colonisation (7967 women), stillbirth and neonatal disease. Whole genome sequencing was used to determine serotypes, sequence types (ST), and phylogeny. We found low maternal GBS colonisation prevalence (934/7967, 12%), but comparatively high incidence of GBS associated stillbirth and early onset neonatal disease (EOD) in hospital (0.91(0.25-2.3)/1000 births; 0.76(0.25-1.77)/1000 live-births respectively). However, using a population denominator, EOD incidence was considerably reduced (0.13(0.07-0.21)/1000 live-births). Treated cases of EOD had very high case fatality (17/36, 47%), especially within 24 hours of birth, making under ascertainment of community-born cases highly likely, both here and in similar facility-based studies. Maternal GBS colonisation was less common in women with low socio-economic status, HIV infection and undernutrition, but when GBS-colonised, they were more likely colonised by the most virulent clone, CC17. CC17 accounted for 267/915(29%) of maternal colonising (265/267(99%) serotype III, 2/267(0.7%) serotype IV), and 51/73(70%) of neonatal disease cases (all serotype III). Trivalent (Ia/II/III) and pentavalent (Ia/Ib/II/III/V) vaccines would cover 71/73(97%) and 72/73(99%) of disease-causing serotypes respectively. Serotype IV should be considered for inclusion, with evidence of capsular switching in CC17 strains.